2020
DOI: 10.1016/j.acra.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Texture Analysis in Alzheimer's disease

Abstract: Texture analysis is an emerging field that allows mathematical detection of changes in MRI signals that are not visible among image pixels. Alzheimer's disease, a progressive neurodegenerative disease, is the most common cause of dementia. Recently, multiple texture analysis studies in patients with Alzheimer's disease have been performed. This review summarizes the main contributors to Alzheimer's disease-associated cognitive decline, presents a brief overview of texture analysis, followed by review of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…(45) This observation is based on the hypothesis that radiomics features, especially second-order features, capture the spatial variation in signal intensity that may re ect the deposition of Aβ plaques. Further, it may extract different biological information from volume, (43,46) which is the traditional imaging biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…(45) This observation is based on the hypothesis that radiomics features, especially second-order features, capture the spatial variation in signal intensity that may re ect the deposition of Aβ plaques. Further, it may extract different biological information from volume, (43,46) which is the traditional imaging biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of MRI texture analyses with machine learning techniques [17], many studies performed classification and prediction of AD. Even though these studies included a greater number of subjects, the vast majority of them focused specifically on the hippocampal region and used only one machine learning technique.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, signal-and texture-related features extracted from MRI scans and selected machine learning techniques have emerged as possible novel markers of AD [17]. In addition, studies of the progression of AD showed that highly asymmetrical contralateral hippocampi and amygdala may indicate an early and accelerated deterioration [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, texture-based analysis, which models local patterns of relative intensity variations rather than the absolute value of intensity, has proven a useful neuroimaging tool. Texture-based analysis can detect group-level differences not evident at the voxel scale (Cai et al, 2020). Unlike a voxel-wise approach, the texture-based analysis aims to describe variations in the patterns of spatial intensity along with a specific orientation.…”
Section: Introductionmentioning
confidence: 99%